Disturbance alters beta‐diversity but not the relative importance of community assembly mechanisms. (2nd July 2015) - Myers, Jonathan A.; Chase, Jonathan M.; Crandall, Raelene M.; Jiménez, Iván; Austin, Amy
Summary Ecological disturbances are often hypothesized to alter community assembly processes that influence variation in community composition (β‐diversity). Disturbance can cause convergence in community composition (low β‐diversity) by increasing niche selection of disturbance‐tolerant species. Alternatively, disturbance can cause divergence in community composition (high β‐diversity) by increasing habitat filtering across environmental gradients. However, because disturbance may also influence β‐diversity through random sampling effects owing to changes in the number of individuals in local communities (community size) or abundances in the regional species pool, observed patterns of β‐diversity alone cannot be used to unambiguously discern the relative importance of community assembly mechanisms. We compared β‐diversity of woody plants and inferred assembly mechanisms among unburned forests and forests managed with prescribed fires in the Missouri Ozarks, USA. Using a null‐model approach, we compared how environmental gradients influenced β‐diversity after controlling for differences in local community size and regional species abundances between unburned and burned landscapes. Observed β‐diversity was higher in burned landscapes. However, this pattern disappeared or reversed after controlling for smaller community size in burned landscapes. β‐diversity was higher than expected by chance in both landscapes, indicating an important role for processes that create clumped species distributions. Moreover, fire appeared to decrease clumping of species at broader spatial scales, suggesting homogenization of community composition through niche selection of disturbance‐tolerant species. Environmental variables, however, explained similar amounts of variation in β‐diversity in both landscapes, suggesting that disturbance did not alter the relative importance of habitat filtering. Our results indicate that contingent responses of communities to fire reflect a combination of fire‐induced changes in local community size and scale‐dependent effects of fire on species clumping across landscapes. Synthesis. Although niche‐based mechanisms of community assembly are often invoked to explain changes in community composition following disturbance, our results suggest that these changes also arise through random sampling effects owing to the influence of disturbance on community size. Comparative studies of these processes across disturbed ecosystems will provide important insights into the ecological conditions that determine when disturbance alters the interplay of deterministic and stochastic processes in natural and human‐modified landscapes.